PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TEH POCI DI KALANGAN MAHASISWA - Roswinna, Winna; Bastari , Ary; Kisahwan, Daniel; Ridwan, Susan; Azzahra, Nazwa; Mulyani, Mila; Melinda, Melinda; Agustin, Lidya (Journal of Sustainable Agribusiness, 2025)
Teh Poci is one of the popular packaged beverage products among university students due to its practicality, affordability, and easy availability. Amid the variety of beverage options in the market, it is important to understand how students as consumers make purchasing decisions and what factors influence their behavior. This study aims to analyze student consumer behavior in purchasing decisions of Teh Poci by examining five main aspects: decision-making process, motivation, perception, attitude, and social and cultural influences.This research uses a descriptive qualitative approach with observation and interviews conducted with five students from Universitas Winaya Mukti who actively consume Teh Poci. The results show that purchasing decisions are influenced by the need for a practical and refreshing drink, affordable price, and easy product access around the campus. Additionally, social influences such as peer encouragement and group consumption culture also play a role in purchasing decisions.It can be concluded that students' purchasing behavior toward Teh Poci is influenced by a combination of internal and external factors, reflecting the typical consumption characteristics of student life.